Gadopentetate dimeglumine enhancement of multiple sclerosis lesions on long TR spin-echo images at 0.6 T. - Barkhof, F; Valk, J; Hommes, O R; Scheltens, P; Nauta, J J (American Journal of Neuroradiology, 1992)
The authors sought to determine if Gd-DTPA enhancement of multiple sclerosis (MS) hampers lesion detection on long TR spin-echo images (TE 60 msec) at 0.6 T. They measured the signal intensity (SI) of 41 lesions (10 patients) and normal-appearing gray (NAGM) and white matter (NAWM) before and after administration of contrast. The change in SI of nonenhancing lesions and NAGM and NAWM was small (less than or equal to 1.5%), and of enhancing lesions (5.3%) moderate. The contrast of nonenhancing lesions to NAGM and NAWM changed insignificantly, but the contrast of enhancing lesions to NAGM and NAWM increased significantly. The authors conclude that long TR images can be obtained after Gd-DTPA without hampering lesion conspicuity in research MR protocols in multiple sclerosis.